Determination of 16 Phthalic Acid Esters in Medical Infusion Plastic Bottles by GC-MS - Zhong, Hao; Ge, De-Zhou; Deng, Zu-Lei; Ma, Tao; Liu, Hao (Asian Journal of Chemistry, 2015)
To establish a gas chromatograph mass spectrometer method for the determination of 16 phthalic acid esters (PAEs) in medical infusion plastic bottles. Sample pretreatment procedures involved of dichloromethane as extraction solvent and ultrasonic extraction method. There was a good linearity range of related 16 phthalic acid esters was observed. The correlation coefficient was ranged at 0.9907-0.9998. Low detection limits of 0.02-0.09 μg g-1. The mean recoveries were in the range from 82.3 to 101.6 % at 8 and 1 μg g-1 spiked levels and the relative standard deviations were in the range of 1.12 and 4.86 % (n = 6). Meanwhile, phthalic acid esters were determined in 40 medical infusion plastic bottles from four pharmaceutical companies in Bengbu city of Anhui province of China. The survey of 40 samples showed dimethyl phthalate, diisobuthyl phthalate and dicyclohexyl phthalate had 100 % (40:40), 87.5 % (35:40) and 45 % (18:40) detection rate. The dimethyl phthalate, diisobuthyl phthalate and dicyclohexyl phthalate were detected at the range of 0.06-0.6 μg g-1, which indicated that more attention should be paid to the phthalic acid esters in medical infusion plastic bottles.